Anomalies of the fickian diffusion during 2D-decomposition of superconducting YBa 2 Cu 3 O 6+X /Y 2 BaCuO 5 composites - Nechaev, Yury S. (Diffusion Fundamentals, 2006)
Based on a thermodynamic analysis of the relevant experimental data, some anomalies of the diffusion mass-transport during two dimensional (2D) decompositioning high-temperature superconducting (HTSC) cuprates are considered. Possible mechanism for the manifestation of phase fluctuation-like effects in the HTSC cuprates, especially with respect to the physical properties of melt-textured composites, thin films, coatings, nanomaterials and heterostructures are discussed.